CHARACTERISTICS OF VICTIMOGENEOUS FACTORS OF THE CRIME OF AGGRESSION AGAINST UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the analysis of victimogenic factors of the crime of aggression against Ukraine. The external-colonial (historically and geographically determined relations between Russia and Ukraine) and the internal contour of victimization factors have been established, given a description and explanation. In the structure of the latter, the destructive role of strategic deficiencies in the arms control system is emphasized: excessive and uncontrolled sale of arms, unjustified write-offs, embezzlement; anti-state actions with a mobilization reserve; crime in the defense-industrial complex; oligarchization The description of the external (international) contour of victimogenic factors is provided: strategic underestimation of the scale of expansionist claims of the Russian Federation and the degree of military threats; shortcomings of coalition actions after 2014 and, to a greater extent, after February 24, 2022.